Epidemiology of major limb amputations: a cross sectional study from a South Indian tertiary care hospital - P., Unnikrishnan E.; Rollands, Rakesh; Parambil, Sasi M. (International Surgery Journal, 2017)
Background: Limb loss to amputation is a major problem especially in developing countries where majority of the cases are preventable. It is a burden, not just for the patient, but also for their care givers which imposes tremendous financial and psychological burden upon them. The aim was to outline the patterns, indications and short term complications of major limb among patients attending Government Medical College, Kozhikode, Kerala, India which is a tertiary care centre. Methods: This was a prospective, observational study that was conducted at Govt. Medical College, Kozhikode, for a period of 18 months. 81 patients underwent major limb amputations in our hospital during the study period. Results: The age ranged between 23 to 90 years (mean 59.23±14.79). Males outnumber females by a ratio of 4:1. Above knee (transtibial) amputations were the most common. Diabetes mellitus was the most common cause (39.5%) followed by chronic NDMVI (33.3%). Younger individuals who underwent amputation were mostly due to trauma. Most common post op complication was surgical site infection (21%) and the most common organism cultured from the wound was Pseudomonas (50%). The most common additional procedure done was wound debridement. The mortality rate was 10% and mean duration of hospital stay was 23 days. Conclusions: Complications of diabetic foot ulcers and chronic vascular disease were the most common indications for major limb amputation in our environment. Trauma was the most common indication in younger individuals. The majority of these amputations are preventable by provision of health education, early presentation and appropriate management of the common indications.